Modified Transformerless Boost Derived Hybrid Converter with no Right Half-Plane Zero and Reduced Leakage Current - Samal S.K.; Singh R.K.; Mahanty R. (My University, 2025)
In this paper a minimum phase system is presented by eliminating the right half-plane zero (RHPZ) from the control-to-dc output transfer function in modified transformerless boost derived hybrid converter (MTLBDHC) for hybrid outputs. The minimum phase behavior has been achieved without using any magnetically coupled inductors in the input side of the hybrid converter. Further, the proposed topology is able to provide both AC and DC loads simultaneously from a single source of supply. Moreover, the proposed MTLBDHC is also able to minimize the harmful common ground leakage current, when it is either connected to the utility grid or the inverter output neutral point is grounded. Detailed mathematical modeling along with the small signal analysis of the proposed MTLBDHC is carried out in this article. Finally, to verify the performance of the proposed MTLBDHC, a 350 W down-scaled laboratory prototype is developed. © 2022 IEEE.